The Role of Green Accounting and Carbon Emission Disclosure in Increasing Firm Value - Supriyanti, Erly; Wardhani, Nurhastuty Kesumo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research analyzes the role of green accounting and carbon emission disclosure in determining firm value. The population in the study consisted of companies that participated in the Company Performance Assessment Program in Environmental Management (PROPER) organized by the Ministry of Environment and Forestry (KLHK) during the 2020-2023 period. This research uses a purposive sampling technique in determining the sample with a sample size of 20 companies each year and is processed with the help of SPSS 25. This research uses multiple linear regression analysis to test the effect of green accounting and carbon emission disclosure on firm value. The research results indicate that green accounting significantly impacts firm value, and foreign ownership as a moderating variable strengthens the substantial and positive relationship between green accounting and firm value. Meanwhile, the carbon emission disclosure variable indicates that the results are insignificant to firm value.